THE EFFECTIVENESS OF EDUCATION, SKILLS, ATTITUDE AND COMMUNICATION ON JOB PROMOTIONS AT LORIN SOLO HOTEL - Deny Irawan; Bambang Mursito; Ida Aryati Diyah Purnomo (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Job Promotion is an appreciation from the company as a form of appreciation to employees for working well and maximally. An important reason the company must provide selection to its employees, so that the employees selected for promotion have higher quality than other employees. This is done so that employees have the motivation to upgrade themselves to be better. The purpose of this study was to determine the effect of Education, Skills, Attitudes and Communication on Job Promotion at Lorin Solo Hotel. This research was conducted using primary data as many as 135 respondents who are employees at Lorin Solo Hotel. The technique used is descriptive quantitative which uses questionnaires, interviews and literature studies. The data collection uses a questionnaire with a Likert scale. The test used multiple linear regression analysis and performed classical assumption test and data quality test. The results of the study concluded that Education, Attitudes and Communication had a positive effect on Position Promotion. Meanwhile, skills have no effect on promotion of positions at Lorin Solo Hotel. Simultaneously Education, Skills, Attitudes and Communication have an effect on Position Promotion where F count > F table is 5.059 2.4388. The value of determination (R2) is 50.8% Keywords : Education, Skill, Attitude, Communication, Job Promotions